2020
DOI: 10.22159/ajpcr.2020.v13i9.38401
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude, and Practice Regarding Hypothyroidism Among Infertile Women With Hypothyroidism

Abstract: Objective: The study was designed to assess the knowledge, attitude, and practice (KAP) of hypothyroidism among infertile women with hypothyroidism. Methods: A cross-sectional analysis was performed in an outpatient environment of infertility centers. We used a validated questionnaire to assess hypothyroidism KAP. Using frequency counts (n) and percentages (%), discrete data were summarized. The Chi-square/Fisher test was used between groups to compare. Results: The mean age of participants was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Prasanna et al found similar findings among infertile females with hypothyroidism. 20 Age and educational status were associated with attitude in our study, which is similar to that study too. 20 Maheshwari et al found that more than half of the study population had incorrect knowledge, beliefs, and practice that improved after education.…”
Section: Table-v: Associations Of Knowledge Attitude and Practice Dom...supporting
confidence: 92%
See 3 more Smart Citations
“…Prasanna et al found similar findings among infertile females with hypothyroidism. 20 Age and educational status were associated with attitude in our study, which is similar to that study too. 20 Maheshwari et al found that more than half of the study population had incorrect knowledge, beliefs, and practice that improved after education.…”
Section: Table-v: Associations Of Knowledge Attitude and Practice Dom...supporting
confidence: 92%
“…20 Age and educational status were associated with attitude in our study, which is similar to that study too. 20 Maheshwari et al found that more than half of the study population had incorrect knowledge, beliefs, and practice that improved after education. 21 The practice domain showed that more than one-third of the females with hypothyroidism forgot to check the expiry date before buying levothyroxine.…”
Section: Table-v: Associations Of Knowledge Attitude and Practice Dom...supporting
confidence: 92%
See 2 more Smart Citations